Augmented Reality in Education (Journal of Information Technology and Digital World, 2020)
Gaining from books is an unremarkable and latent cycle. The content and images in the books are most certainly not interactive; this prompts the basic barricades to learning looked by students, for example, constraints in comprehending the hypothetical ideas, absence of explanatory, basic reasoning. These detours are overwhelmed by computerized books, however paper-based books are frequently favored over computerized books due to their adaptability and portability. In this paper, we present a remarkable arrangement that utilizes augmented reality to make the learning measure more interactive and fascinating. The application when focused on text or image shows significant 3-dimensional(3D) model or video on the smart phone screen. The application gives some assistance to the students by encouraging them to learn new ideas utilizing graphical guide. Aside from utilization in schooling, it can likewise be utilized in the field of commercial, the travel industry, gaming, medication.
Keywords: Augmented Reality; education; learning